Linkage Between Radar Reflectivity Slope and Raindrop Size Distribution in Precipitation with Bright Bands - Li, Qinghui; Sun, Xuejin; Liu, Xichuan; Li, Haoran (Remote sensing (Basel, Switzerland), 2025)
This study investigates the linkage between the radar reflectivity slope and raindrop size distribution (DSD) in precipitation with bright bands through coordinated C-band/Ka-band radar and disdrometer observations in southern China. Precipitation is classified into three types based on the reflectivity slope (K-value) below the freezing level, revealing distinct microphysical regimes: Type 1 (K = 0 to −0.9) shows coalescence-dominated growth; Type 2 (|K| > 0.9) shows the balance between coalescence and evaporation/size sorting; and Type 3 (K = 0.9 to 0) demonstrates evaporation/size-sorting effects. Surface DSD analysis demonstrates distinct precipitation characteristics across classification types. Type 3 has the highest frequency of occurrence. A gradual decrease in the mean rain rates is observed from Type 1 to Type 3, with Type 3 exhibiting significantly lower rainfall intensities compared to Type 1. At equivalent rainfall rates, Type 2 exhibits unique microphysical signatures with larger mass-weighted mean diameters (Dm) compared to other types. These differences are due to Type 2 maintaining a high relative humidity above the freezing level (influencing initial Dm at bottom of melting layer) but experiencing limited Dm growth due to a dry warm rain layer and downdrafts. Type 1 shows opposite characteristics—a low initial Dm from the dry upper layers but maximum growth through the moist warm rain layer and updrafts. Type 3 features intermediate humidity throughout the column with updrafts and downdrafts coexisting in the warm rain layer, producing moderate growth.